Reservoir evaporation prediction modeling based on artificial intelligence methods - Allawi M.F. (MDPI AG, 2023)
Forecasting; Network architecture; Radial basis function networks; Tropics; Artificial intelligence methods; Climatic conditions; Climatic parameters; Prediction accuracy; Prediction model; Radial basis function neural networks; Support vector regression (SVR); Tropical environmental; Evaporation; accuracy assessment; artificial intelligence; climate conditions; climate effect; evaporation; hydrological modeling; methodology; prediction; reservoir; tropical environment; Johor; Johor River; Layang Reservoir; Malaysia; West Malaysia